Short term subjective outcomes of lateral fracture as a complementary treatment of coblation turbinoplasty in traumatized nose - Pier Giorgio Giacomini; Francesco Maria Passali; Barbara Flora; Valentina Rosati; Stefano Di Girolamo (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Inferior turbinate compensatory hypertrophy is a common condition found in post-traumatic septal deviation. In literature several approaches are described for treating turbinates enlargment. We conduct a retrospective study on two group of 43 and 48 patients mached for age and sex that underwent to rino-septo-turbinoplasty from January 2011 to January 2013. First group was treated by inferior turbinates submucous unipolar coblation and the second by submucous unipolar coblation plus lateral outfracture. Inclusion criteria were: isolated nasal occlusion non-sensitive to medical treatment with compensatory enlarged inferior turbinate/s and marked nasal pyramid-septal deviation evaluated by pre-operative nasal endoscopy; turbinates hypertrophic grade from I -III according to Friedman.  "Functional" results were graded by subjective pre- and post-operative evaluation (3 and 6 months after surgery) using SF-12 and NOSE scoring systems. Turbinate volume reduced significantly (CHI square test, p<0.001) post-operatively. Grade III score from more than 1/3 of patients pre-op falls to none post-op (p<0.001). Grade II reduces from 58% to 23%. Grade I sharply increase from none pre-op to 72% post-op. These data remain grossly unchanged at 6 months endoscopy. 69/91 (83%) patients were satisfied by surgical results on nasal breathing checked by SF-12 (p < 0.01) at 3 and 6 months post-operatively. The NOSE pre-operative scoring reduced significantly post-op. (65.6 vs 22.8, p< 0.001), early and late post-op results are similar but an increase of scores is recorded overtime.  No significant (over one minute) lengthening of surgical time was ever recorded due to the lateral outfracture of the conchal bone. A wider nasal passage by nasal endoscopy after coblation plus outfracture vs simple coblation was observed but the NOSE scores improved similarly in both groups. The lateral outfracture of the turbinate may improve the volume of air passage through the nose without increasing of complication rates or healing time.